2014
DOI: 10.1007/s11912-014-0402-4
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of HPV-Associated Anogenital Cancers

Abstract: The epidemiology of anogenital cancers is under going substantial change. Cervical cancer remains a major public health concern, particular in resource-limited settings. Cancers of the anus, penis, vagina and vulva are relatively uncommon cancers, but may be increasing in incidence. The change in occurrence of anogenital cancers may be due to increasing HPV transmission secondary to changes in sexual behaviour. Screening programmes and the HPV vaccine offer optimism that anogenital cancers can be prevented. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 97 publications
3
60
1
3
Order By: Relevance
“…These findings are consistent with previous work in Scotland which showed that the European age-standardised ratio for VSCC between 1972-1976 and 2007-2011, increased from 3.3 per 100,000 to 4.2 per 100,000 and that this increase was most prominent among younger women. 3 These data also reconcile with the US study, which assessed VSCC data from nine US Cancer registries for the period 1973-2004 and showed that VIN and VSCC increased 3.5% and 1.0% respectively, each year with the increase observed in all categories but the largest increase occurred in women aged 54 or less. 22 Reasons for this phenomenon are unclear at present.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These findings are consistent with previous work in Scotland which showed that the European age-standardised ratio for VSCC between 1972-1976 and 2007-2011, increased from 3.3 per 100,000 to 4.2 per 100,000 and that this increase was most prominent among younger women. 3 These data also reconcile with the US study, which assessed VSCC data from nine US Cancer registries for the period 1973-2004 and showed that VIN and VSCC increased 3.5% and 1.0% respectively, each year with the increase observed in all categories but the largest increase occurred in women aged 54 or less. 22 Reasons for this phenomenon are unclear at present.…”
Section: Discussionsupporting
confidence: 70%
“…2, 3 The reasons behind the changing epidemiology of vulval disease are unclear but it may be driven by a secular increase in HPV infection and/or changed behaviors that have facilitated the transmission.…”
Section: Introductionmentioning
confidence: 99%
“…HPV is best known for its role in causing nearly 100% of cases of cervical cancer, which is the fourth most common cancer in women [1,2]. In addition, HPV has been indicated to be a human biologic carcinogen for 5 other types of cancers: penile, vaginal, vulvar, anal, and oropharynx including the base of the tongue and tonsils, with a high percentage of oropharyngeal cancer cases in the United States being attributed to HPV [14]. …”
Section: Introductionmentioning
confidence: 99%
“…High-risk human papilloma virus is a well-established causative agent of a component of oropharyngeal carcinomas and cancers of the anogenital tract including cervical cancer 5. The association of HPV-16 and carcinomatous transformation was extended to the conjunctiva in 1989 when McDonnell and coworkers identified the virus in all patients investigated with conjunctival SCC 17.…”
Section: Discussionmentioning
confidence: 99%
“…The steps in HPV-driven carginogenesis include infection, persistence of infection, progression to premalignant lesions and invasion 5. In the absence of invasive disease, precursor lesions can be reversible.…”
Section: Introductionmentioning
confidence: 99%